Optimal Design of Ultra-Premium Efficiency Synchronous Reluctance Motor - Boztas, Gullu; Aydogmus, Omur; Caner, Murat (Ieee, 2019)
The current study presents an optimal design of a Synchronous Reluctance Motor (SynRM) in Ultra-Premium Efficiency IE5 class. The motor was designed and optimized using MAGNET for Finite Element Analysis (FEA) and MATLAB for optimization. A multi-objective optimization method was used in order to achieve maximum torque and minimum torque ripple at the steady-state operation. Stator slot tooth width, rotor web thickness and rotor flux barriers were optimized and the other parameters were kept constant during the optimization. The optimized motor was also analyzed using PWM analyzing method in MotorSolve program for efficiency. According to the IEC TS 60034-30-2:2016 report, the designed motor was determined in IE5 efficiency class. However, it can be said that the designed motor can be easily manufactured in IE4 class.
11th International Conference on Electrical and Electronics Engineering (ELECO) -- NOV 28-30, 2019 -- Bursa, TURKEY
Keywords: Induction-Motors; Improvement; Tracking; Optimization; Algorithm; Drive